The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2096531120928084
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Good and Functioning Well in Mathematics Education: Exploring Students’ Conceptions of Mathematical Well-Being and Values

Abstract: Purpose: The high incidence of mathematics anxiety and disengagement in mathematics points to poor student well-being in many mathematics classrooms. Poor well-being may arise in part from poor alignment between student values and classroom experiences. Yet, what student well-being is and how to support it within specific subjects is poorly understood, and intersection between students’ values and well-being in mathematics education is unclear. This article proposes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…As researchers have noticed, the issues about values in mathematics education are rather complex (e.g., Hill et al, 2021), and this complexity is largely caused by the complexity of the concept of values itself. In fact, when people talk about "values" in mathematics education, what are valued can be mathematics, mathematics teaching and learning, and mathematics education as part of general education, and those who value can be students, teachers, curriculum developers, educational policy makers, government leaders, and the general public or the society, and moreover, values can be about the outcomes of teaching and learning or about their process.…”
Section: Discussion and Concluding Remarks: Issues And Future Directionsmentioning
confidence: 99%
“…As researchers have noticed, the issues about values in mathematics education are rather complex (e.g., Hill et al, 2021), and this complexity is largely caused by the complexity of the concept of values itself. In fact, when people talk about "values" in mathematics education, what are valued can be mathematics, mathematics teaching and learning, and mathematics education as part of general education, and those who value can be students, teachers, curriculum developers, educational policy makers, government leaders, and the general public or the society, and moreover, values can be about the outcomes of teaching and learning or about their process.…”
Section: Discussion and Concluding Remarks: Issues And Future Directionsmentioning
confidence: 99%
“…Given the increase in interest in students' wellbeing in school education, not least due to the COVID-19 pandemic, the close links between values and (mathematical) wellbeing (e.g. Tiberius, 2018) have been investigated in Australia, led by Julia Hill (Hill et al, 2021), and more recently in China (Pan et al, in press), further highlighting the significance of values and valuing in helping students learn mathematics more effectively and positively. Yet, we have not fully developed efficient means of inculcating specific values amongst students.…”
Section: Valuesmentioning
confidence: 99%
“…Unfortunately, the argument by Hill, Kern, Seah and van Driel (2020) that there is "a poor sense of student well-being in many Australian mathematics classrooms" (p. 2) would apply to most if not all countries around the world. Students are generally not thriving in their mathematics learning experience, and not feeling good nor happy with it as well.…”
Section: )mentioning
confidence: 99%
“…A recent Australian study conducted by Hill, Kern, Seah and van Driel (2020) had aimed to explore if there might be a set of values that is relatively stable at the national level. Preliminary findings from 488 Grade 8 students in Melbourne suggested that the following seven 'themes' were associated with positive wellbeing: relationships, engagement, cognitive, accomplishment, positive emotions, perseverance, and meaning.…”
Section: )mentioning
confidence: 99%